Pre-Raphaelite Food Politics or, Feasting on Desire: John Everett Millais, Social Norms and Women - Lidia Mihaela NECULA (Cultural Intertexts)
Renowned for his infamous painting Christ in the House of his Parents (1849-1850) or for The Tragic Story of Ophelia (1851-1852) which brought him domestic and international fame during his lifetime as a British painter, John Everett Millais (1829-1896) is known as one of the founders of the Pre-Raphaelite Brotherhood (1848), a group of young and idealistic artists determined to instil vibrating energy and novelty into contemporary art which they considered to have been stifled by the prevailing conventions of the Royal Academy. Millais’s works display microscopic attention to pictorial realism and manifest an almost fetishistic attention to photographic detail; and yet, it is despite this covert technique (or maybe particularly due to it!) that Millais’ art manifests a certain politics springing from an exceptional daring in the way his paintings function as genuine social and cultural parables. Therein, the current paper looks into three of Millais’ paintings (namely, Bridesmaid (1851), Isabella (1868), and The Captive (1882)), as mirrors that reflect and challenge while obliquely commenting on and criticising Victorian social norms (particularly those related to gender, gender roles, binary oppositions and desire) through the depiction of food. Hence, the main focus of the paper is not merely uncovering Millais’ food aesthetics and the way he uses food as a subject of aesthetic interest but rather looking into Millais’ food politics (and poetics) and the way food becomes a vehicle for expressing deeper societal concerns, class distinctions, moral lessons, and cultural exchanges.